1977
DOI: 10.1128/aem.34.6.701-705.1977
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the etiological agent of primary amoebic meningoencephalitis from artifically heated waters

Abstract: To determine whether artificial heating of water by power plant discharges facilitates proliferation of the pathogenic free-living amoebae that cause primary amoebic meningoencephalitis, water samples (250 ml) were taken from discharges within 3,000 feet (ca. 914.4 m) of power plants and were processed for amoeba culture. Pathogenic Naegleria fowleri grew out of water samples from two of five lakes and rivers in Florida and from one of eight man-made lakes in Texas. Pathogenic N. fowleri did not grow from wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Proliferation of N. fowleri and other free-living amoebae have been known for decades to occur best between 30-42°C (Jamerson et al 2009;Stevens et al 1977;_ Zbikowska et al 2013). N. fowleri has also been shown to tolerate temperatures up to 45°C, although with limited survival when compared to cultures grown at the optimum 37°C (Stevens et al 1977;Tsvetkova et al 2004). Thermophily is a relatively unique trait in the Naegleria genus.…”
Section: Figurementioning
confidence: 99%
“…Proliferation of N. fowleri and other free-living amoebae have been known for decades to occur best between 30-42°C (Jamerson et al 2009;Stevens et al 1977;_ Zbikowska et al 2013). N. fowleri has also been shown to tolerate temperatures up to 45°C, although with limited survival when compared to cultures grown at the optimum 37°C (Stevens et al 1977;Tsvetkova et al 2004). Thermophily is a relatively unique trait in the Naegleria genus.…”
Section: Figurementioning
confidence: 99%
“…Five other species are known in the genus Naegleria, i.e.N, gruberi, N. jadini, N. andersoni, N. lovaniensis and N. australiensis; but fowled and to a less extent, N. australiensis. N. fowleri has been isolated from various bodies of water [2], particularly from those submitted to thermal pollution [3]. The disease is acquired by inhalation of water containing the amoebae: N.…”
Section: Introductionmentioning
confidence: 99%
“…However, among the different sampling points the pH varied from 6.91 to 7.94 ( Table 1). pH of tap water close to neutrality [42] showed that free-living amoebae were able to grow in vitro at a pH range of 5.6-8.4 [43][44].…”
Section: Resultsmentioning
confidence: 99%